(untitled) (Research, Society and Development, 2021)
Objective: To analyze the perspectives of students in teaching and learning about the human aging process with a view to educational action. Methodology: This is an exploratory-descriptive qualitative approach research. Consisting of three phases: identification and selection of students able to participate in the study, individual interviews with script of questions and recording of answers and transcription of the speeches and answers in full for grouping thoughts. Results: The development of the teaching and learning process was observed in various aspects inherent to this phenomenon based on the views and subjectivity of students, categorizing classes with institutional, teacher, student and subjective scopes to learning and professional work in the human aging process. Conclusion: In the context of the research, the potential and difficulties present in the educational aspects of the aging process from the student perspective became evident, providing an opportunity to understand how this process of training and performance in nursing is constituted.